Role of Cefiderocol in Multidrug-Resistant Gram-Negative Central Nervous System Infections: Real Life Experience and State-of-the-Art - Alessio Sollima; Francesco Rossini; Paola Lanza; Carlo Pallotto; Marianna Meschiari; Ivan Gentile; Roberto Stellini; Angelica Lenzi; Alice Mulé; Francesca Castagna; Silvia Lorenzotti; Silvia Amadasi; et al. (MDPI AG, 2024)
Cefiderocol is a new molecule effective against multidrug-resistant (MDR) Gram-negative pathogens. Currently, there is limited evidence regarding the use of cefiderocol in central nervous system (CNS) infections. Data on the cerebrospinal fluid penetration rate of cefiderocol are limited and heterogeneous, and there is no consensus on the dosing scheme of cefiderocol to penetrate the blood-brain barrier. We present a case series and a literature review of CNS infections caused by MDR pathogens that were treated with cefiderocol: some of these patients were treated with different dose schemes of cefiderocol and underwent therapeutic drug monitoring both on plasma and cerebrospinal fluid (CSF). The CSF penetration rates and the clinical outcomes were evaluated.